A high entropy garnet oxide solid electrolyte material and preparation method thereof

By introducing high entropy concepts and multi-site cation co-doping technology into garnet oxide materials, the problems of insufficient ionic conductivity and unstable preparation process of existing garnet LLZO solid electrolytes are solved, and the preparation of high-entropy garnet oxide solid electrolyte materials with high ionic conductivity and low energy consumption are achieved.

CN119208716BActive Publication Date: 2025-04-22UNIV OF SCI & TECH BEIJING
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411700754.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-22
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The ionic conductivity of the existing garnet-type LLZO solid electrolyte has not yet reached the commercialization level. The traditional solid-phase method has a long sintering cycle, high energy consumption, and unstable preparation process.

Method used

High-entropy garnet oxide material is used to prepare a high-entropy garnet oxide solid electrolyte material with high ionic conductivity through multi-site cation co-doping strategy and wet synthesis technology. This method introduces a variety of elements, resulting in lattice distortion, reducing the diffusion energy barrier of Li+, thereby improving ionic conductivity.

Benefits of technology

It significantly improves the ionic conductivity of high-entropy garnet oxide solid electrolyte, reduces sintering temperature and cycle, reduces energy consumption, and improves the stability and performance uniformity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208716B_ABST
    Figure CN119208716B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of lithium battery technology, specifically a high entropy garnet oxide solid electrolyte material and its preparation method, which introduces the concept of "high entropy" into the oxide solid electrolyte, uses lattice distortion to increase the configuration entropy of the material body, promotes the formation of a stable phase, and effectively overcomes the problem of low ion conductivity of the oxide solid electrolyte. By doping with heterovalent ions, the Li inside the structure can be replaced. + , the generation of Li vacancies significantly reduces the Li + The diffusion energy barrier can further improve the ionic conductivity of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a high-entropy garnet-type oxide solid electrolyte material and a preparation method thereof. Background Art

[0002] Currently, lithium-ion batteries generally rely on organic electrolytes or gel electrolytes, which have safety hazards such as flammability and internal short circuits. In contrast, the introduction of inorganic solid electrolytes has built a solid defense line for the safety of lithium-ion batteries. Garnet-type Li7La3Zr2O 12 (LLZO) oxide solid electrolyte not only fundamentally improves the safety of the battery, but also exhibits a higher ionic conductivity, which can reach 10 at room temperature. -4 ~10 -3 S / cm. In addition, garnet-type LLZO solid electrolytes also have the advantages of a wide electrochemical stability window, excellent lithium stability and a simple preparation process. Although many breakthroughs and progress have been achieved in the field of garnet-type oxide solid electrolytes, there are still many core and key issues that urgently need to be explored and resolved. For example, the ionic conductivity of LLZO-type solid electrolytes needs to be further improved to reach commercial levels. In addition, the traditional solid-phase method has the problems of long sintering cycle and poor timeliness, and requires high-temperature sintering, and the energy consumption is significantly high. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a high entropy garnet-type oxide solid electrolyte material and a preparation method thereof.

[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0005] A high entropy garnet oxide solid electrolyte material, the chemical formula of which is: Li γ A α La 3-β B β Zr 2-λ C λ O 12 ;

[0006] Among them, A is at least one of Al, Fe, Ge, and Ga elements, B is at least one of Ca, Sr, Ba, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Ce elements, and C is at least one of Mg, Sc, Hf, Ta, Nb, Ti, Mo, Sb, Zn, Ru, W, and Te elements; and 5.32<γ<7, 0<α≤0.3, 0<β≤0.6, and 0<λ≤0.6.

[0007] As a preferred embodiment of the high entropy garnet oxide solid electrolyte material of the present invention, the ionic conductivity of the high entropy garnet oxide solid electrolyte material is ≥3.45×10 -4 S cm -1 .

[0008] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:

[0009] A method for preparing a high entropy garnet oxide solid electrolyte material comprises the following steps:

[0010] S1. According to the target chemical formula of the high entropy garnet oxide solid electrolyte material, calculate and weigh the required metal salt and organic acid chelating agent as raw materials, wherein the metal salt includes at least lithium salt, lanthanum salt and zirconium salt;

[0011] S2, mixing lithium salt, lanthanum salt and raw materials required for doping on lithium sites and lanthanum sites and dissolving them in solvent 1 to form solution A or suspension A; mixing zirconium salt and raw materials for doping on zirconium sites and dissolving them in solvent 2 to form solution B or suspension B; organic acid chelating agent is dissolved in deionized water to form solution C;

[0012] S3, adding solution A or suspension A to solution B or suspension B to form solution D or suspension D, adding solution C to solution D or suspension D, and dropping ethylene glycol into solution D or suspension D, heating and stirring to obtain sol E;

[0013] S4, allowing Sol E to stand and age at room temperature to form a wet gel;

[0014] S5, drying the wet gel to obtain a dry gel of a solid electrolyte precursor, and grinding the dry gel to obtain a solid electrolyte precursor powder;

[0015] S6, subjecting the precursor powder to a high-temperature debinding process to convert it into a pre-burned powder, then allowing the pre-burned powder to naturally cool to room temperature in the furnace, taking it out and performing a tableting process to obtain a high-entropy oxide electrolyte green blank;

[0016] S7. Place the green body in a muffle furnace and perform the initial high-temperature sintering by a powder embedding method to obtain a high-entropy garnet-type oxide solid electrolyte ceramic sheet; after the ceramic sheet is cooled to room temperature with the furnace, place it in an air atmosphere for a secondary high-temperature sintering treatment to finally obtain a high-entropy garnet-type oxide solid electrolyte material with a dense structure.

[0017] As a preferred embodiment of the method for preparing a high entropy garnet oxide solid electrolyte material described in the present invention, wherein: in the step S1, the lithium salt is at least one of lithium nitrate, lithium carbonate, lithium acetate, lithium hydroxide, lithium chloride, and lithium oxalate; the lanthanum salt is at least one of lanthanum nitrate, lanthanum chloride, lanthanum acetate, lanthanum carbonate, and lanthanum hydroxide; the zirconium source is at least one of zirconium oxynitrate, zirconium oxychloride, and zirconium chloride; and the organic acid chelating agent is at least one of citric acid, oxalic acid, acetic acid, tartaric acid, lauric acid, ascorbic acid, sulfonic acid, and salicylic acid.

[0018] As a preferred embodiment of the method for preparing a high entropy garnet oxide solid electrolyte material described in the present invention, wherein: in step S1, the molar ratio of the organic acid chelating agent to the metal ion is (1.0~3.0):1.

[0019] As a preferred embodiment of the method for preparing a high entropy garnet oxide solid electrolyte material according to the present invention, wherein: in step S1, the amount of lithium salt added is 1.0 to 1.3 times the calculated amount.

[0020] As a preferred embodiment of the method for preparing a high entropy garnet-type oxide solid electrolyte material described in the present invention, wherein: in the step S2, solvent 1 is at least one of deionized water, ethanol, propanol, acetone, n-hexane, isooctane, N-methylpyrrolidone, and N,N-dimethylformamide; solvent 2 is at least one of deionized water, ethanol, propanol, acetone, n-hexane, isooctane, N-methylpyrrolidone, and N,N-dimethylformamide.

[0021] As a preferred embodiment of the method for preparing a high entropy garnet oxide solid electrolyte material described in the present invention, wherein: in the step S3, the molar ratio of ethylene glycol to metal ions is (1.5~3.0):1, the dropping speed is 0.04~0.05mL / s, the heating temperature is 60~100°C, and the stirring time is 8~12h.

[0022] As a preferred embodiment of the method for preparing a high entropy garnet oxide solid electrolyte material according to the present invention, wherein: in the step S4, the sol E is aged at room temperature for 12 to 24 hours.

[0023] As a preferred embodiment of the method for preparing a high entropy garnet oxide solid electrolyte material described in the present invention, wherein: in the step S5, the drying treatment is: drying at 150-250° C. for 2-12 hours.

[0024] As a preferred embodiment of the method for preparing a high entropy garnet oxide solid electrolyte material described in the present invention, wherein: in step S6, the high-temperature debinding process is: heating to 600-800°C at a heating rate of 2-10°C / min in an air atmosphere and keeping the temperature for 3-6 hours, and then cooling with the furnace; the tableting process is: after mixing the pre-sintered powder and the binder, the pressure is maintained at 10-12MPa for 1-10 minutes. The tableting process is carried out in a mold with an inner diameter of 10mm; the binder is preferably polyvinyl butyral (PVB), polyvinyl alcohol (PVA), polyethylene glycol (PEG) solution; the solvent of the binder is preferably ethanol, and the mass percentage of the binder solution is preferably 2-5wt%.

[0025] As a preferred embodiment of the method for preparing a high entropy garnet oxide solid electrolyte material described in the present invention, wherein: in the step S7, the powder embedding method is: placing the green blank into a crucible covered with pre-fired powder, and covering the surface of the green blank with pre-fired powder to prevent the green blank from sticking; the initial high-temperature sintering treatment is: heating to 800~1000℃ at a heating rate of 2~10℃ / min in an air atmosphere, keeping warm for 4~6h, and then cooling with the furnace; the secondary high-temperature sintering treatment is: heating to 900~1300℃ at a heating rate of 2~10℃ / min in an air atmosphere, keeping warm for 6~12h, and then cooling with the furnace.

[0026] The beneficial effects of the present invention are as follows:

[0027] The present invention proposes a high entropy garnet oxide solid electrolyte material and a preparation method thereof, which introduces the concept of "high entropy" into oxide solid electrolytes, uses lattice distortion to increase the configuration entropy of the material body, promotes the formation of a stable phase, and effectively overcomes the problems of low ion conductivity of oxide solid electrolytes. By doping with heterovalent ions, the Li inside the structure can be replaced. + , the generation of Li vacancies significantly reduces the Li + The diffusion energy barrier can further improve the ionic conductivity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0029] Figure 1 This is an impedance curve diagram of the solid electrolyte material prepared in Example 1 of the present invention.

[0030] Figure 2This is the XRD characteristic spectrum of the solid electrolyte material prepared in Example 1 of the present invention.

[0031] Figure 3 This is an impedance curve diagram of the solid electrolyte material prepared in Comparative Example 1 of the present invention.

[0032] Figure 4 This is the XRD characteristic spectrum of the solid electrolyte material prepared in Comparative Example 1 of the present invention.

[0033] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0034] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The main purpose of the present invention is to propose a high-entropy garnet-type oxide solid electrolyte material and a preparation method thereof, adopting a multi-site cation co-doping strategy and relying on wet synthesis technology, aiming to significantly improve the ion conductivity of the obtained high-entropy garnet-type oxide solid electrolyte material.

[0036] The various elements introduced into the crystal structure of the present invention trigger the differences in the size and ionic bond energy of adjacent atoms, thereby causing local structural distortion within the lattice. The obvious local distortion effect directly adjusts the Li +The occupied sites significantly reduce the activation energy required for its migration, thereby effectively improving the ionic conductivity of the garnet-type high entropy oxide solid electrolyte. In particular, the introduction of elements such as tantalum, gallium, titanium, and aluminum as effective dopants not only strengthens the stability of the cubic phase structure of garnet-type LLZO, and improves the shrinkage rate and relative density to a certain extent, but also significantly improves the ionic conductivity of the electrolyte material. In this process, organic acids are used as chelating agents to exert their powerful metal ion coordination ability, promote the rapid formation of stable and uniform metal ion complexes, and lay a solid foundation for the preparation of high-quality precursors. At the same time, ethylene glycol is introduced as an efficient dispersant, which effectively promotes the dissolution and uniform distribution of metal ions in the solution system, significantly improves the dispersibility and consistency of materials, and further promotes the smooth progress of the sol-gel process, which is crucial for building a stable and uniform precursor structure. Through the above-mentioned optimized preparation method, the present invention introduces a variety of metal elements into the lattice to prepare a cubic phase material with pure crystal phase and uniform distribution height. On the basis of maintaining the stable structure of cubic garnet, the unique thermodynamic high entropy effect of high entropy materials is fully utilized to significantly enhance the cubic phase stability of the material. At the same time, local distortion also helps to form a good ion migration path. Thus, the prepared high entropy garnet oxide solid electrolyte Li γ A α La 3-β B β Zr 2-λ C λ O 12 , its ionic conductivity is improved compared with the traditional LLZO electrolyte.

[0037] The present invention successfully uses the sol-gel method to integrate a variety of metal elements into the material system, and successfully synthesizes a cubic phase high entropy oxide material, which exhibits significantly improved ionic conductivity characteristics. Compared with the traditional solid phase method, the sol-gel method shows significant advantages in ensuring the uniform distribution of each element, and achieves a high uniformity of doped elements. With the fine regulation of the sol-gel method and the unique advantages of the high entropy effect, the elements in the precursor reach a uniform mixed state, which ensures that the final product-cubic phase garnet oxide material has a pure and single crystal phase, and also achieves a uniform distribution of particle size and optimizes the microstructure of the material. In addition, the implementation of the sol-gel method not only greatly reduces the sintering temperature, shortens the sintering cycle, effectively improves production efficiency, but also significantly reduces energy consumption, which is in line with the core concept of green manufacturing. At the same time, due to the flexibility and variability of the wet process steps, the boundaries of element doping are broadened, providing unlimited possibilities for the continuous optimization of the performance of solid electrolyte materials.

[0038] According to one aspect of the present invention, the present invention provides the following technical solution:

[0039] A high entropy garnet oxide solid electrolyte material, the chemical formula of which is: Li γ A α La 3-β B β Zr 2-λ C λ O 12 ;

[0040] Among them, A is at least one of Al, Fe, Ge, and Ga elements, B is at least one of Ca, Sr, Ba, Pr, Nd, Sm, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Y, and Ce elements, and C is at least one of Mg, Sc, Hf, Ta, Nb, Ti, Mo, Sb, Zn, Ru, W, and Te elements; and 5.32<γ<7, 0<α≤0.3, 0<β≤0.6, and 0<λ≤0.6.

[0041] Preferably, the ionic conductivity of the high entropy garnet oxide solid electrolyte material is ≥3.45×10 -4 S cm -1 .

[0042] According to another aspect of the present invention, the present invention provides the following technical solution:

[0043] A method for preparing a high entropy garnet oxide solid electrolyte material comprises the following steps:

[0044] S1. According to the target chemical formula of the high entropy garnet oxide solid electrolyte material, calculate and weigh the required metal salt and organic acid chelating agent as raw materials, wherein the metal salt includes at least lithium salt, lanthanum salt and zirconium salt;

[0045] S2, grinding the metal salt, mixing the lithium salt, lanthanum salt and the raw materials required for doping on the lithium site and the lanthanum site and dissolving them in solvent 1 to form a solution A or a suspension A; mixing the zirconium salt and the raw materials for doping on the zirconium site and dissolving them in solvent 2 to form a solution B or a suspension B; dissolving the organic acid chelating agent in deionized water to form a solution C;

[0046] S3, adding solution A or suspension A to solution B or suspension B to form solution D or suspension D, adding solution C to solution D or suspension D, and dropping ethylene glycol into solution D or suspension D, heating and stirring to obtain sol E;

[0047] S4, allowing Sol E to stand and age at room temperature to form a wet gel;

[0048] S5, drying the wet gel in an air drying oven to obtain a dry gel of a solid electrolyte precursor, and grinding the dry gel to obtain a solid electrolyte precursor powder;

[0049] S6, subjecting the precursor powder to a high-temperature debinding process to convert it into a pre-burned powder, then allowing the pre-burned powder to naturally cool to room temperature in the furnace, taking it out and performing a tableting process to obtain a high-entropy oxide electrolyte green blank;

[0050] S7. Place the green body in a muffle furnace and perform the initial high-temperature sintering by a powder embedding method to obtain a high-entropy garnet-type oxide solid electrolyte ceramic sheet; after the ceramic sheet is cooled to room temperature with the furnace, place it in an air atmosphere for a secondary high-temperature sintering treatment to finally obtain a high-entropy garnet-type oxide solid electrolyte material with a dense structure.

[0051] Preferably, in step S1, the lithium salt is at least one of lithium nitrate, lithium carbonate, lithium acetate, lithium hydroxide, lithium chloride, and lithium oxalate; the lanthanum salt is at least one of lanthanum nitrate, lanthanum chloride, lanthanum acetate, lanthanum carbonate, and lanthanum hydroxide; the zirconium source is at least one of zirconium oxynitrate, zirconium oxychloride, and zirconium chloride; and the organic acid chelating agent is at least one of citric acid, oxalic acid, acetic acid, tartaric acid, lauric acid, ascorbic acid, sulfonic acid, and salicylic acid.

[0052] Preferably, in step S1, the molar ratio of the organic acid chelating agent to the metal ion is (1.0-3.0):1.

[0053] Preferably, in step S1, the amount of lithium salt added is 1.1 to 1.3 times the calculated amount. Excess lithium salt is added to compensate for the volatilization of lithium during high-temperature sintering.

[0054] Preferably, in step S2, solvent 1 is at least one of deionized water, ethanol, propanol, acetone, n-hexane, isooctane, N-methylpyrrolidone, and N,N-dimethylformamide; solvent 2 is at least one of deionized water, ethanol, propanol, acetone, n-hexane, isooctane, N-methylpyrrolidone, and N,N-dimethylformamide.

[0055] Preferably, in step S3, the molar ratio of ethylene glycol to metal ions is (1.5-3.0):1, the dropping speed is 0.04-0.05 mL / s, the heating temperature is 60-100° C., and the stirring time is 8-12 h.

[0056] Preferably, in step S4, the sol E is allowed to stand and age at room temperature for 12 to 24 hours.

[0057] Preferably, in step S5, the drying process is: drying at 150-250° C. for 2-12 hours. The grinding process uses an agate mortar for grinding for 10-20 minutes.

[0058] Preferably, in step S6, the high-temperature debinding process is: heating to 600-800°C at a heating rate of 2-10°C / min in an air atmosphere and keeping the temperature for 3-6 hours, and then cooling with the furnace; the tableting process is: mixing the pre-sintered powder and the binder, and keeping the pressure at 10-12MPa for 1-10 minutes. The tableting process is carried out in a mold with an inner diameter of 10mm; the binder is preferably polyvinyl butyral (PVB), polyvinyl alcohol (PVA), polyethylene glycol (PEG) solution; the solvent of the binder is preferably ethanol, and the mass percentage of the binder solution is preferably 2-5wt%.

[0059] Preferably, in step S7, the powder embedding method is: placing the green blank into a crucible covered with pre-fired powder, and covering the surface of the green blank with the pre-fired powder to prevent the green blank from sticking; the initial high-temperature sintering treatment is: heating to 800~1000℃ at a heating rate of 2~10℃ / min in an air atmosphere, keeping warm for 4~6h, and then cooling with the furnace; the secondary high-temperature sintering treatment is: heating to 900~1300℃ at a heating rate of 2~10℃ / min in an air atmosphere, keeping warm for 6~12h, and then cooling with the furnace.

[0060] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0061] Example 1

[0062] This example is used to prepare Li 6.4 Ga 0.2 Al 0.1 La 2.5 Sr 0.5 Zr 1.8 Ta 0.2 O 12 A high-entropy garnet oxide solid electrolyte, comprising the following processes:

[0063] S1. Weigh 1.457 g lithium nitrate, 0.251 g gallium nitrate, 0.113 g aluminum nitrate, 3.248 g lanthanum nitrate, 0.318 g strontium nitrate, 1.735 g zirconium oxynitrate and 0.133 g tantalum oxide, and grind them separately, wherein the lithium nitrate is in excess of 10 wt.% to compensate for the loss of lithium during high temperature sintering;

[0064] S2. After grinding the raw materials, lithium nitrate, gallium nitrate, aluminum nitrate, lanthanum nitrate and strontium nitrate are mixed and dissolved in deionized water to form a solution A; zirconium oxynitrate and tantalum oxide are mixed and dissolved in deionized water to form a suspension B; 15.559 g of citric acid is weighed and dissolved in deionized water to form a solution C;

[0065] S3, adding solution A to suspension B to form suspension D; then adding solution C to suspension D, and dropping ethylene glycol into suspension D at a rate of 0.05 mL / s to ensure sufficient dispersion and mixing of the substances, and stirring at 80° C. for 10 h to obtain a sol;

[0066] S4, placing the sol at room temperature and aging it for 12 hours to form a wet gel;

[0067] S5. Place the wet gel in a 200° C. forced air drying oven and dry for 6 hours to obtain a dry gel of LGALSZTO high entropy oxide solid electrolyte precursor, and grind to obtain LGALSZTO high entropy oxide solid electrolyte precursor powder.

[0068] S6. The precursor powder is heated to 750°C at a heating rate of 5°C / min and kept warm for 6 hours for debinding treatment, and the pre-burned powder is obtained after cooling in the furnace; after mixing 1g of the pre-burned powder with 0.2g of a solution containing 2wt% PEG, the mixture is pressed at a pressure of 11MPa for 5min to obtain a high entropy oxide electrolyte blank.

[0069] S7. Heat the green blank to 800°C at a heating rate of 3°C / min in an air atmosphere and keep it warm for 5 hours to perform powder burying sintering to obtain a LGALSZTO high entropy oxide solid electrolyte ceramic sheet; after the ceramic sheet is cooled to room temperature with the furnace, it is placed in an air atmosphere again, and the temperature is increased to 1050°C at a heating rate of 3°C / min and kept warm for 6 hours to obtain the LGALSZTO high entropy oxide solid electrolyte material.

[0070] Figure 1 This is the room temperature impedance curve of the high entropy garnet solid electrolyte material prepared in this example. The ionic conductivity can be calculated to be 3.47×10 -4 S cm -1 . Figure 2 Demonstrated in Example 1 the high entropy garnet oxide solid electrolyte material Li 6.4 Ga 0.2 Al 0.1 La 2.5 Sr 0.5 Zr 1.8 Ta 0.2 O 12 The XRD pattern of the product matches that of PDF#80-0457, confirming that the product is a typical cubic garnet phase structure. The slight shift of the characteristic peaks in the spectrum can be attributed to the change in the lattice constant caused by the introduction of the doping element.

[0071] Example 2

[0072] This example is used to prepare Li 6.2Ga 0.1 Fe 0.1 Ln3Z 1.5 Ti 0.3 Ta 0.2 O 12 A high-entropy garnet oxide solid electrolyte, comprising the following processes:

[0073] S1. Weigh 1.411 g lithium nitrate, 0.126 g gallium nitrate, 0.081 g ferric chloride, 3.897 g lanthanum nitrate, 1.446 g zirconium oxynitrate, 0.072 g titanium oxide and 0.133 g tantalum oxide, and grind them separately, wherein the lithium nitrate is in excess of 10 wt% to compensate for the loss of lithium during high temperature sintering.

[0074] S2. After grinding the raw materials, lithium nitrate, gallium nitrate, ferric chloride and lanthanum nitrate are mixed and dissolved in deionized water to form a solution A; zirconium oxynitrate, titanium oxide and tantalum oxide are mixed and dissolved in deionized water to form a suspension B; 15.156 g of citric acid is weighed and dissolved in deionized water to form a solution C;

[0075] S3, adding solution A to suspension B to form suspension D; then adding solution C to suspension D, and dropping ethylene glycol into suspension D at a rate of 0.05 mL / s to ensure sufficient dispersion and mixing of the substances, and stirring at 85° C. for 9 h to obtain a sol;

[0076] S4, placing the sol at room temperature and aging it for 14 hours to form a wet gel;

[0077] S5. Place the wet gel in a 180° C. forced air drying oven and dry for 11 h to obtain a dry gel of a LGFLZTTO high entropy oxide solid electrolyte precursor. Grind the dry gel to obtain a LGFLZTTO high entropy oxide solid electrolyte precursor powder.

[0078] S6. The precursor powder is heated to 700°C at a heating rate of 5°C / min and kept warm for 6 hours for debinding treatment, and the pre-burned powder is obtained after cooling in the furnace; after mixing 1g of the pre-burned powder with 0.2g of a solution containing 2wt% PEG, the mixture is pressed at a pressure of 10MPa for 3min to obtain a high entropy oxide electrolyte blank.

[0079] S7. Heat the green blank to 850°C at a heating rate of 3°C / min in an air atmosphere and keep it warm for 5 hours to perform powder burying sintering to obtain a LGALSZTO high entropy oxide solid electrolyte ceramic sheet; after the ceramic sheet is cooled to room temperature with the furnace, it is placed in an air atmosphere again, and the temperature is increased to 1050°C at a heating rate of 3°C / min and kept warm for 6 hours to obtain the LGALSZTO high entropy oxide solid electrolyte material.

[0080] Example 3

[0081] This example is used to prepare Li 6.1 Al 0.1 Ga 0.15 Fe 0.1 La 2.6 Sr 0.4 Zr 1.5 Ti 0.25 Ta 0.25 O 12 A high-entropy garnet oxide solid electrolyte, comprising the following processes:

[0082] S1. Weigh 1.388 g lithium nitrate, 0.113 g aluminum nitrate, 0.188 g gallium nitrate, 0.081 g ferric chloride, 3.378 g lanthanum nitrate, 0.254 g strontium nitrate, 1.446 g zirconium oxynitrate, 0.06 g titanium oxide and 0.166 g tantalum oxide, and grind them separately, wherein the lithium nitrate is in excess of 10 wt% to compensate for the loss of lithium during high temperature sintering.

[0083] S2. After grinding the raw materials, lithium nitrate, aluminum nitrate, gallium nitrate, ferric chloride, lanthanum nitrate and strontium nitrate are mixed and dissolved in deionized water to form a solution A; zirconium oxynitrate, titanium oxide and tantalum oxide are mixed and dissolved in deionized water to form a suspension B; 15.206 g of citric acid is weighed and dissolved in deionized water to form a solution C;

[0084] S3, adding solution A to suspension B to form suspension D; then adding solution C to suspension D, and dropping ethylene glycol into suspension D at a rate of 0.05 mL / s to ensure sufficient dispersion and mixing of the substances, and stirring at 70° C. for 12 h to obtain a sol;

[0085] S4, placing the sol at room temperature and aging it for 15 hours to form a wet gel;

[0086] S5, placing the wet gel in a 220° C. forced air drying oven and drying for 6 h to obtain a dry gel of LAGFLSZTTO high entropy oxide solid electrolyte precursor, and grinding to obtain LAGFLSZTTO high entropy oxide solid electrolyte precursor powder;

[0087] S6. The precursor powder is heated to 800°C at a heating rate of 5°C / min and kept warm for 3 hours for debinding treatment, and the pre-burned powder is obtained after cooling in the furnace; after mixing 1g of the pre-burned powder with 0.2g of a solution containing 2wt% PEG, the mixture is pressed at a pressure of 10MPa for 5min to obtain a high entropy oxide electrolyte blank.

[0088] S7. Heat the green blank to 900°C at a heating rate of 3°C / min in an air atmosphere and keep it warm for 4 hours to perform powder burying sintering to obtain LGALSZTO high entropy oxide solid electrolyte ceramic sheet; after the ceramic sheet is cooled to room temperature with the furnace, it is placed in an air atmosphere again, and the temperature is increased to 650°C at a heating rate of 3°C / min and kept warm for 2 hours, and then the temperature is continued to be increased to 1050°C and kept warm for 6 hours to obtain LGALSZTO high entropy oxide solid electrolyte material.

[0089] Comparative Example 1

[0090] This comparative example is used to prepare Li7La3Zr2O 12 The solid electrolyte comprises the following processes:

[0091] S1. Weigh 1.593 g lithium nitrate, 3.897 g lanthanum nitrate and 1.928 g zirconium oxynitrate and grind them separately, wherein the lithium nitrate is in excess of 10 wt % to compensate for the loss of lithium during high temperature sintering.

[0092] S2. After grinding the raw materials, lithium nitrate and lanthanum nitrate are mixed and dissolved in deionized water to form solution A; zirconium oxynitrate is dissolved in deionized water to form solution B; 16.013 g of citric acid is weighed and dissolved in deionized water to form solution C;

[0093] S3, adding solution A to solution B to form solution D; then adding solution C to solution D, and dropping ethylene glycol into solution D at a rate of 0.05 mL / s to ensure sufficient dispersion and mixing of the substances, and stirring at 80° C. for 10 h to obtain a sol;

[0094] S4, placing the sol at room temperature and aging it for 12 hours to form a wet gel;

[0095] S5, placing the wet gel in a 200° C. forced air drying oven for 6 h to obtain a dry gel of LLZO precursor, and grinding the dry gel to obtain LLZO precursor powder;

[0096] S6. The precursor powder is heated to 750°C at a heating rate of 5°C / min and kept warm for 6 hours for debinding treatment, and the pre-burned powder is obtained after cooling in the furnace; after mixing 1g of the pre-burned powder with 0.2g of a solution containing 2wt% PEG, the mixture is pressed at a pressure of 11MPa for 5 minutes to obtain an oxide electrolyte blank.

[0097] S7. Heat the green blank to 950°C at a heating rate of 3°C / min in an air atmosphere and keep it warm for 4 hours to perform powder burying sintering to obtain a LGALSZTO high entropy oxide solid electrolyte ceramic sheet; after the ceramic sheet is cooled to room temperature with the furnace, it is placed in an air atmosphere again, and the temperature is increased to 1050°C at a heating rate of 3°C / min and kept warm for 6 hours to obtain the LGALSZTO high entropy oxide solid electrolyte material.

[0098] Figure 3 The room temperature impedance curve of the solid electrolyte material prepared in this comparative example shows that the ionic conductivity is 1.26×10 -4 S cm -1 . Figure 4 The garnet oxide solid electrolyte material Li7La3Zr2O in Comparative Example 1 is clearly presented. 12 The XRD spectrum of the electrolyte is shown in Figure 1. The characteristic peaks in the spectrum match the cubic garnet structure, indicating that the electrolyte is a cubic garnet phase, but there are a small amount of La2Zr2O7 impurity peaks, and the presence of these peaks has a certain impact on the performance of the electrolyte.

[0099] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A high entropy garnet oxide solid electrolyte material, characterized in that: Its chemical formula is: Li γ A α La 3-β B β Zr 2-λ C λ O 12 ; Wherein, A is Ge, B is at least one of Yb and Ce, and C is at least one of Ta, Ti, Sb, Zn and Te; and 5.32<γ<7, 0<α≤0.3, 0<β≤0.6, 0<λ≤0.6; lattice distortion is used to increase the configuration entropy of the material body and promote the formation of a stable phase; its ionic conductivity is ≥3.45×10 -4 S cm -1 .

2. A method for preparing the high entropy garnet oxide solid electrolyte material according to claim 1, characterized in that: The steps include: S1. According to the target chemical formula of the high entropy garnet oxide solid electrolyte material, calculate and weigh the required metal salt and organic acid chelating agent as raw materials, wherein the metal salt includes at least lithium salt, lanthanum salt and zirconium salt; S2, mixing lithium salt, lanthanum salt and raw materials required for doping on lithium sites and lanthanum sites and dissolving them in solvent 1 to form solution A or suspension A; mixing zirconium salt and raw materials for doping on zirconium sites and dissolving them in solvent 2 to form solution B or suspension B; organic acid chelating agent is dissolved in deionized water to form solution C; S3, adding solution A or suspension A to solution B or suspension B to form solution D or suspension D, adding solution C to solution D or suspension D, and dropping ethylene glycol into solution D or suspension D, heating and stirring to obtain sol E; S4, allowing Sol E to stand and age at room temperature to form a wet gel; S5, drying the wet gel to obtain a dry gel of a solid electrolyte precursor, and grinding the dry gel to obtain a solid electrolyte precursor powder; S6, subjecting the precursor powder to a high-temperature debinding process to convert it into a pre-burned powder, then allowing the pre-burned powder to naturally cool to room temperature in the furnace, taking it out and performing a tableting process to obtain a high-entropy oxide electrolyte green blank; S7. Place the green body in a muffle furnace and perform the initial high-temperature sintering by a powder embedding method to obtain a high-entropy garnet-type oxide solid electrolyte ceramic sheet; after the ceramic sheet is cooled to room temperature with the furnace, place it in an air atmosphere for a secondary high-temperature sintering treatment to finally obtain a high-entropy garnet-type oxide solid electrolyte material with a dense structure.

3. The method for preparing the high entropy garnet oxide solid electrolyte material according to claim 2, characterized in that: In step S1, the lithium salt is at least one of lithium nitrate, lithium carbonate, lithium acetate, lithium chloride, and lithium oxalate; the lanthanum salt is at least one of lanthanum nitrate, lanthanum chloride, lanthanum acetate, and lanthanum carbonate; the zirconium source is at least one of zirconium oxynitrate, zirconium oxychloride, and zirconium chloride; and the organic acid chelating agent is at least one of citric acid, oxalic acid, acetic acid, tartaric acid, lauric acid, ascorbic acid, sulfonic acid, and salicylic acid.

4. The method for preparing a high entropy garnet oxide solid electrolyte material according to claim 2, characterized in that: In step S1, the molar ratio of the organic acid chelating agent to the metal ion is (1.0-3.0):

1.

5. The method for preparing a high entropy garnet oxide solid electrolyte material according to claim 2, characterized in that: In step S2, solvent 1 is at least one of deionized water, ethanol, propanol, acetone, n-hexane, isooctane, N-methylpyrrolidone, and N,N-dimethylformamide; solvent 2 is at least one of deionized water, ethanol, propanol, acetone, n-hexane, isooctane, N-methylpyrrolidone, and N,N-dimethylformamide.

6. The method for preparing a high entropy garnet oxide solid electrolyte material according to claim 2, characterized in that: In step S3, the molar ratio of ethylene glycol to metal ions is (1.5-3.0):1, the dropping speed is 0.04-0.05 mL / s, the heating temperature is 60-100° C., and the stirring time is 8-12 h.

7. The method for preparing a high entropy garnet oxide solid electrolyte material according to claim 2, characterized in that: In the step S4, the sol E is allowed to stand and age at room temperature for 12 to 24 hours.

8. The method for preparing a high entropy garnet oxide solid electrolyte material according to claim 2, characterized in that: In step S5, the drying process is: drying at 150-250° C. for 2-12 hours.

9. The method for preparing a high entropy garnet oxide solid electrolyte material according to claim 2, characterized in that: In step S6, the high-temperature debinding process is: heating to 600-800°C at a heating rate of 2-10°C / min in an air atmosphere and keeping the temperature for 3-6 hours, and then cooling with the furnace; the tableting process is: after mixing the pre-burned powder and the binder, keeping the pressure at 10-12 MPa for 1-10 minutes.

10. The method for preparing a high entropy garnet oxide solid electrolyte material according to claim 2, characterized in that: In step S7, the powder embedding method is: placing the green blank into a crucible covered with pre-fired powder, and covering the surface of the green blank with the pre-fired powder to prevent the green blank from sticking; the initial high-temperature sintering treatment is: heating to 800~1000℃ at a heating rate of 2~10℃ / min in an air atmosphere, keeping warm for 4~6h, and then cooling with the furnace; the secondary high-temperature sintering treatment is: heating to 900~1300℃ at a heating rate of 2~10℃ / min in an air atmosphere, keeping warm for 6~12h, and then cooling with the furnace.

Citation Information

Patent Citations

  • Preparation method of solid electrolyte material

    CN115863748A

  • Garnet type oxide solid electrolyte, preparation method and application thereof

    CN116683021A

  • Nano lithium lanthanum zirconium oxygen-based powder as well as preparation method and application thereof

    CN117756175A

  • KR20230028110A